A methods engineering study on National Kidney and Transplant Institute - Cortez, Kahna (College of Engineering, 2001)
A Methods Engineering Study is conducted in the National Kidney and Transplant Institute. NKTI is presently the only hospital that specializes in renal diseases and organ transplantations. it is located along East Avenue, Quezon City. The use of a streamline analysis diagram and work sampling analysis made the group conclude the following problems : improper time allocated to nurses activities and strained workload for nurses. An Ishikawa diagram was done to determine the root causes for these problems. The root causes of both problems are : too much paperwork and inappropriate staffing level. A solution to too much paperwork is the revision of the nurses' progress notes. This will cost NKTI the expense of discarding its present forms and the printing of the alternative forms. Nurses will have to be oriented in the implementation of these new forms. It is also recommended for NKTI to go back to their original staffing level of a 12 hour shift with the number of staff personnel they have in order to maximize their workforce efficiently. This is to be implemented as soon as possible because the old staff is still familiar with it and can help orient the new nurses regarding how to go about this new schedule. Another recommendation is to provide an educational seminar for proper body mechanics to ease the strain of the nurses' workload. Studies have shown that lifting patients and equipment causes back injuries for nurses. This seminar will be very helpful to the nurses in NKTI. The cost of such seminar will require the cost of research regarding this matter. NKTI has a department focused on nurses' training called NISTER that can handle the logistics of this project.